California’s Comprehensive Perinatal Services Program and birth outcomes - Lopes, Snehal S.; Shi, Ahan; Chen, Liwei; Li, Jian; Meschke, Laurie L. (Frontiers in Public Health, 2023)
Introduction California’s Medicaid (Medi-Cal) sponsors Comprehensive Perinatal Services Program (CPSP), a program with enhanced perinatal care for women (more education, nutritional supplements, and psychosocial counseling/support). Past evaluations of CPSP’s effectiveness in birth outcomes were limited to pilot programs and yielded mixed results. Methods We used 2012–2016 California’s statewide data about singleton live births with any receipt of prenatal care (N = 2,385,811) to examine whether Medi-Cal with CPSP enrollment was associated with lower odds of preterm birth (PTB), spontaneous PTB, and low birthweight (LBW) than non-CPSP births. With three binary variables of PTB, spontaneous PTB, and LBW as the response variables, three multilevel logistic models were used to compare the outcomes of participants enrolled in Medi-Cal with CPSP against those with private insurance, adjusting for maternal factors and county-level covariates. Results Logistic models showed that participants enrolled to Medi-Cal with CPSP [n (%) = 89,009 (3.7)] had lower odds of PTB, spontaneous PTB and LBW, respectively, as compared with those with private insurance [n (%) = 1,133,140 (47.2)]. Within the Medi-Cal sub-population, the CPSP enrollment was associated with lower odds of PTB, SPTB and LBW than Medicaid beneficiaries without CPSP [n (%) = 967,094 (40.3)]. Discussion With statewide data, these findings revealed a robust link between CPSP enrollment and better birth outcomes. Expanding access to comprehensive prenatal services could be an important strategy to improve birth outcomes.